2013
DOI: 10.1186/1748-717x-8-103
|View full text |Cite
|
Sign up to set email alerts
|

Selective use of postoperative neck radiotherapy in oral cavity and oropharynx cancer: a prospective clinical study

Abstract: BackgroundIn cervical postoperative radiotherapy, the target volume is usually the same as the extension of the previous dissection. We evaluated a protocol of selective irradiation according to the risk estimated for each dissected lymph node level.MethodsEighty patients with oral/oropharyngeal cancer were included in this prospective clinical study between 2005 and 2008. Patients underwent surgery of the primary tumor and cervical dissection, with identification of positive nodal levels, followed by selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
1
6
0
2
Order By: Relevance
“…Thus, different approaches should be made to improve the clinical results for patients with oral cavity or recurrent disease. In this study, the most frequent site of regional recurrence was the high-risk CTV (70 %), similar results showed with Carrillo et al [ 15 ]. Out of field regional recurrence was observed more frequently in ipsilateral neck than contralateral neck whereas only one patient developed contralateral-neck failure.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, different approaches should be made to improve the clinical results for patients with oral cavity or recurrent disease. In this study, the most frequent site of regional recurrence was the high-risk CTV (70 %), similar results showed with Carrillo et al [ 15 ]. Out of field regional recurrence was observed more frequently in ipsilateral neck than contralateral neck whereas only one patient developed contralateral-neck failure.…”
Section: Discussionsupporting
confidence: 91%
“…Later on, selective neck dissection (SND) was introduced which preserved one or more lymph node levels [ 10 ] and the development of common terminology of discriminating neck levels which was well-known as the classification of American Head and Neck Society (AHNS) followed [ 11 , 12 ]. However, the applicability of the concept of the selective nodal irradiation in postoperative setting is controversial [ 13 15 ]. Gregoire et al [ 13 ] and Chao et al [ 14 ] proposed the clinical target volume (CTV) guidelines for postoperative neck region, but the authors admitted the paucity of data on which one could create a specific guideline for postoperative CTV.…”
Section: Introductionmentioning
confidence: 99%
“…В исследовании Carrillo et al [24] по результатам регионарной лимфодиссекции были идентифицированы три клинических объема для регионарных ЛУ: CTV0, CTV1 и CTV2 с риском поражения <10%, 10-25% и 25% с предписанной дозой <35 Гр, 50 Гр и 66-70 Гр соответственно. Рецидивы в зоне высокого риска (CTV1 CTV2) диагностированы в 12 случаях, рецидивы в маргинальной зоне (CTV1/ CTVO) -в 1, вне зоны облучения -в 2 случаях.…”
Section: материалы и методыunclassified
“…Трехлетний регионарный контроль составил 80%. Результаты такого селективного послеоперационного облучения регионарных ЛУ оказались сопоставимы со стандартным объемом облучения при меньшем риске осложнений [24]. Эти данные свидетельствуют о том, что преимущества дифференцированного подведения различного уровня доз к клиническим объемам в зависимости от риска рецидива могут быть реализованы при точной идентификации этих объемов, что, в свою очередь, возможно при тесном взаимодействии специалистов на всех этапах лечения.…”
Section: материалы и методыunclassified
“…Although historically, the neck has been included in irradiating mid‐line OCSCC, there is growing evidence that postoperative radiotherapy (PORT) can be omitted safely in pN0 neck as the risk of occult metastases in surgically negative necks is low. Carrillo et al 4 reported that selected neck radiation postoperatively, in OCSCC and oropharyngeal primaries was safe and there were only 2.7% failures in unirradiated neck nodes. This resulted in an improved acute toxicity (16% Grade 3 OM and 14% grade 3 dysphagia).…”
mentioning
confidence: 99%